2020
DOI: 10.3390/cells9102307
|View full text |Cite
|
Sign up to set email alerts
|

GUN1 and Plastid RNA Metabolism: Learning from Genetics

Abstract: GUN1 (genomes uncoupled 1), a chloroplast-localized pentatricopeptide repeat (PPR) protein with a C-terminal small mutS-related (SMR) domain, plays a central role in the retrograde communication of chloroplasts with the nucleus. This flow of information is required for the coordinated expression of plastid and nuclear genes, and it is essential for the correct development and functioning of chloroplasts. Multiple genetic and biochemical findings indicate that GUN1 is important for protein homeostasis in the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Recently, the variegated phenotype was also observed in cotyledons of ftsh2 and ftsh5 seedlings upon introgression of the gun1 knock-out mutation (for further details see Tadini et al [ 16 ]). GUN1 is a chloroplast-localized pentatricopeptide repeat (PPR) protein required during the early stages of chloroplast biogenesis and upon alterations of plastid gene expression and chloroplast protein homeostasis [ 16 , 17 , 18 , 19 , 20 , 21 ]. In particular, gun1 ftsh2 cotyledons are characterized by the presence of highly vacuolated plastids, without any traces of thylakoid membranes, while gun1 ftsh5 cotyledons show a less severe albino-variegated phenotype and possess cells with either functional chloroplasts or plastids with budding vesicles, an evidence of the ongoing plastid degradation process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the variegated phenotype was also observed in cotyledons of ftsh2 and ftsh5 seedlings upon introgression of the gun1 knock-out mutation (for further details see Tadini et al [ 16 ]). GUN1 is a chloroplast-localized pentatricopeptide repeat (PPR) protein required during the early stages of chloroplast biogenesis and upon alterations of plastid gene expression and chloroplast protein homeostasis [ 16 , 17 , 18 , 19 , 20 , 21 ]. In particular, gun1 ftsh2 cotyledons are characterized by the presence of highly vacuolated plastids, without any traces of thylakoid membranes, while gun1 ftsh5 cotyledons show a less severe albino-variegated phenotype and possess cells with either functional chloroplasts or plastids with budding vesicles, an evidence of the ongoing plastid degradation process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, an increased PRPS1 protein accumulation (Fig 6C) could be achieved by introgressing the prps1-1 knockdown allele into prpl11-1 genetic background, in which the chloroplast translation is reduced [42]. This is also in line with the restoration of PRPS1 protein accumulation observed in prps1 gun1 and prps1 rh50 double mutants, as GUN1 stimulates the activity of the Nuclear-Encoded Polymerase (NEP) that, among other plastid house-keeping genes, is responsible of the transcription of clpP1, while RH50 is involved in plastid ribosome assembly and plastid translation [28,52,[93][94][95]. Intriguingly, GUN1 was also found to physically interact with the plastid protein homeostasis machinery, including CLPC subunits [28].…”
Section: Plos Geneticsmentioning
confidence: 60%
“…The very short-half-life of DUF760-2 (minute scale) as compared to the 4-6 hours half-life of DUF760-1 is intriguing. The PPR protein GUN1 (Richter et al, 2023; Shimizu and Masuda, 2021; Tadini et al, 2020; Wu and Bock, 2021) is another example of a chloroplast protein with a demonstrated short half-life (∼4 hours), and interestingly is also dependent of CLPC1 for its degradation (Wu et al, 2019). However, despite tremendous efforts by a number of laboratories there is still no consensus on the direct function of GUN1 (as also reflected in the numerous reviews cited above).…”
Section: Discussionmentioning
confidence: 99%